The Spectrum of Inflammatory and Developmental Odontogenic Cysts - Hassan, Irfan; Naeem, Shagufta; Lakhnana, Noor Khan; Iqbal, Toqueer; Naz, Shabana (International Journal of Pathology, 2018)
Objective: To study the spectrum of inflammatory and developmental odontogenic cysts.Introduction: Epithelial lined cysts of the oral cavity are among the most commonly encountered oral diseasesfrom both the clinicians and pathologists perspective. To reach a specific diagnosis a multi team approach isnecessary which includes radiologists, surgeons and pathologists.Two major categories of cysts exist; odontogenic and non-odontogenic. The most commonly encounteredodontogenic cysts are radicular or periapical cyst; which may occur in any age group but common in 3rd and 4thdecade. The second common type is dentigerous cyst that accounts for 17% of all the odontogenic cysts.Keratocysts account for 10% of all odontogenic cyst and can have more chances of recurrence.Materials and Methods: 60 cases sent to the Pathology Department during Sept. 2006 to Dec 2009 wereincluded in the study, after observing inclusion and exclusion criteria. After gross examination the sections wereroutinely processed and slides stained with H& E. All the slides were thoroughly examined by two consultanthistopathologists and postgraduate pathology resident.Results and conclusions: 50% were radicular cysts, 36% were dentigerous cysts, keratocysts and eruptioncysts accounted for 8% and 5% respectively. In one case of dentigerous cyst ameloblastoma was diagnosed andone case was diagnosed at maxillary antrum, an unusual site for dentigerous cysts.